Accumulation et sous-développement au Zaïre 1960-1980 - Bezy, Fernand; Peemans, Jean-Philippe; Wautelet, Jean-Marie (Louvain-la-Neuve : UCL, 1981)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: economie; Zaïre; Kongo